State of Mangroves in Tiniguiban Cove, Puerto Princesa Bay,Puerto Princesa City, Palawan - Becira, Eunice (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The study State of Mangroves in Tiniguiban Cove, Puerto Princesa Bay, Puerto Princesa City was documented and assessed using the following parameters: total area covered, diversity, population structure and diversity and threats to mangrove (cutting). The study was conducted in May 2003 using plot-quadrat method. Ten plots were non-randomly distributed in the study area. Fourteen major and one associated mangrove species were found in the study area (H=0.85). The three dominant species were Rhizophora apiculata (41% ), Sonneratia alba (39%) and R. stylosa (13%). These species also accordingly, they had the highest importance values at 192, 146, and 80, respectively. Considering the small size of the mangrove stand, diversity was relatively high compared in other areas of Palawan. However, continuous expansion of residential areas as well as the development of various students poses a threat to the survival of mangroves. Thus, demarcation of the present mangrove area in Tiniguiban Cove is needed.